1995
DOI: 10.1159/000282715
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma Presenting as a Large Abdominal Mass with an Extensive Peritoneal Metastasis

Abstract: We report a case of renal cell carcinoma with an extensive intraperitoneal metastasis at the time of diagnosis. This type of metastasis is very rare for renal cell carcinoma and is identified in only 1 % of the metastases at autopsy. The findings of computed tomography are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
1
Order By: Relevance
“…first as presentation with disseminated peritoneal disease, second as recurrence after initial nephrectomy [ 20 ] and third, most common nowadays, as port site and omental mets after the laparoscopic excision of renal masses. Stavropoulos et al reported a case who presented with peritoneal metastasis and noted that the incidence of peritoneal metastasis in renal cell carcinoma is about 1% at autopsy [ 21 ]. The first port site metastasis was probably reported for the first time in 2006 by Dhobada et al [ 22 ], while recurrence in peritoneum was reported in 1990 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…first as presentation with disseminated peritoneal disease, second as recurrence after initial nephrectomy [ 20 ] and third, most common nowadays, as port site and omental mets after the laparoscopic excision of renal masses. Stavropoulos et al reported a case who presented with peritoneal metastasis and noted that the incidence of peritoneal metastasis in renal cell carcinoma is about 1% at autopsy [ 21 ]. The first port site metastasis was probably reported for the first time in 2006 by Dhobada et al [ 22 ], while recurrence in peritoneum was reported in 1990 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Stavropoulos et al proposed a possible mechanism leading to malignant ascites in renal cell cancer 12 , suggesting that growth of renal cancer outside the kidney’s capsule and Gerota’s fascia predisposes to local peritoneal involvement, starting a vicious cycle of ascites formation and more diffuse involvement of the peritoneum. They also described embolic hematogenous metastases involving the omentum, mesentery and peritoneum, initiating the process of development of malignant ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Some aggressive RCC subtypes with adverse histopathological features (sarcomatoid differentiation etc.) can present with diffuse peritoneal metastases involving the omentum [7] , [8] . However, development of metachronous omental metastasis(es), particulary in the absence of diffuse peritoneal involvement, is an extremely rare condition in the natural history of RCC.…”
Section: Discussionmentioning
confidence: 99%